Inventory Physical Count Process: A Best Practice Discourse - Sitraselvi Chandren; Santhirasegaran Nadarajan; Zaimah Abdullah (International Journal of Supply Chain Management, 2015)
The inventory physical count is an activity conducted by firms to confirm and inspect physical inventory balance to book balance. The inventories are one of the major expenditure for the firms particularly the manufacturing industries which materially influence the financial results. For reliable financial results, firms need to organize inventory physical count in effective and efficient manner with best practices for quality inventories balance results. The results of the inventory physical count are essential to firms financial reporting as inventories influence on the firm performance and position. The correctness in inventory balances provides assurance to financial performance and position of firms. Thus, the purpose of this paper is to elaborate on the operational aspect of inventory physical count in terms of roles played by the management and personnel in-charge of inventory physical count and how inventory physical count is organized and conducted from the beginning stage to ending stage. This paper provides a clear understanding of the general inventory physical count process including the best practices for these processes as a strategy to achieve the desired inventory physical count results. This paper will be a guide on inventory physical count processes to academic and practitioners and knowledge to students.